Altruistic punishment in intergroup context - Ünal-Koçaslan, Özge; Akgün, Serap (Springer, 2024)
Experimental studies in the literature have shown that individuals are willing to sacrifice their own resources to punish free-riders even if there is no possibility to get reward for this behavior. The aim of the current study is to examine whether individuals have preferences to punish violators when the punishment is costly for themselves and to test whether this preference is affected by social categorization (i.e., ingroup-outgroup settings). For these aims we conducted two experiments. In both studies the Third-Party Punishment Game was used. Study 1 in which a 2 (distributor’s identity: ingroup vs. outgroup) x 2 (recipient’s identity: ingroup vs. outgroup) x 2 (fairness: equal vs. unequal) within-subjects design was used consists of 38 participants and Study 2 in which a mixed design was used consists of 174 participants. It was found in both studies that participants spent higher amounts to punish unfair players than fair players. Additionally, in Study 2 participants were found to prefer to altruistically punish the perpetrator more harshly when the victim was an ingroup member. The findings suggest that individuals attempt to maintain cooperative behavior norms by engaging in costly punishment of selfish individuals, regardless of their group membership. However, the stricter reactions to unfairness directed to an ingroup member show that participants favor ingroup members over outgroup members in line with the social identity literature. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.
Keywords: Costly punishment; Norm enforcement; Social categorization; Social preferences; Third party